Old Tyrosine Kinase Inhibitors and Newcomers in Gastrointestinal Cancer Treatment - Erika, Giordani; Federica, Zoratto; Martina, Strudel; Anselmo, Papa; Luigi, Rossi; Marina, Minozzi; Davide, Caruso; Eleonora, Zaccarelli; Monica, Verrico; Silverio, Tomao (Current Cancer Drug Targets, 2016)
Gastrointestinal cancer treatment is based more on molecular biology that has provided increasing knowledge about cancer pathogenesis on which targeted therapy is being developed. Precisely, targeted therapy is defined as a “type of treatment that uses drugs, such as monoclonal antibodies or tyrosine kinase inhibitors, to identify and attack specific cancer cells”. Nowadays, the United States Food and Drug Administration has approved many targeted therapies for gastrointestinal cancer treatment, as many are in various phases of development as well. In a previous review we discussed the main monoclonal antibodies used and studied in gastrointestinal cancer. In addition to monoclonal antibodies, tyrosine kinase inhibitors represent another class of targeted therapy and following the approval of imatinib for gastrointestinal stromal tumours, other tyrosine kinase inhibitors have been approved for gastrointestinal cancers treatment such as sunitinib, regoragenib, sorafenib and erlotinib. Moving forward, the purpose of this review is to focus on the efficacy data of main tyrosine kinase inhibitors commonly used in the personalized treatment of each gastrointestinal tumour and to provide a comprehensive overview about experimental targeted therapies ongoing in this setting.
Keywords: Approved tyrosine kinase inhibitors